Quality of life and its correlates in pretreatment patients with locally advanced head and neck cancer: A cross-sectional study in Thailand - Sirinya Pimvichai; Yaowarat Matchim; Tanadej Sinthusake; Kiratiya Wongkalasin (Belitung Raya Foundation, Indonesia, 2023)
Background: Locally advanced head and neck cancer (LAHNC) can significantly impact the quality of life of patients in various ways. However, several factors can contribute to the decrease in quality of life. In Thailand, there is limited knowledge about the factors that affect the quality of life of patients with LAHNC before they receive treatment. Objective: This study aimed to examine the correlations between Palliative Performance Scale (PPS), family income, body mass index (BMI), age, comorbidity index, and the quality of life of patients with LAHNC before they undergo treatment. Methods: A correlational cross-sectional study was conducted, and data were collected from 94 pretreatment patients with LAHNC who were admitted to a cancer center in central Thailand using purposive sampling. The data collection instruments included a demographic data form, a medical record form, the Charlson Comorbidity Index (CCI), the Palliative Performance Scale (PPS), and the Functional Assessment of Cancer Therapy-Head and Neck (FACT-H&N) version 4. Descriptive statistics, Pearson’s correlation, and Spearman’s rank correlation were used to analyze the data. Results: All study participants completed the questionnaire. The results showed that the overall quality of life of the patients was moderate. PPS, family income, and body mass index were moderately positively correlated with quality of life (r = 0.494, p <0.01; r = 0.420, p <0.01; r = 0.339, p<0.01, respectively). Age had a moderate negative correlation with quality of life (r = -0.596, p <0.01), while comorbidity was not significantly associated with quality of life. Conclusion: The quality of life of patients with LAHNC before treatment was associated with various factors, including PPS, family income, body mass index, and age. These findings highlight the importance of nutritional support before treatment and the need for social support, especially for older adult patients, to improve their quality of life. The results of this study can be valuable for nurses in developing care programs that enhance the quality of life for patients with LAHNC during the pretreatment phase.